Biomechanical markers and theoretical concepts related to haemophilic ankle and subtalar joint arthropathy: introducing the term 'haemophilic tarsal pan‐arthropathy'. Issue 4 (17th March 2017) - Lobet, S.; McCarthy, A.; Hermans, C.; Peerlinck, K.; Matricali, G. A.; Staes, F.; Deschamps, K.
Abstract : Background: Although regular factor replacement can reduce the incidence of joint bleeds and slow down the development of haemophilic arthropathy, the ankle joint remains particularly vulnerable even in children with haemophilia on primary or secondary prophylaxis and is now the primary joint affected. The heterogeneity in the pathoaetiology of haemophilic ankle arthropathy means that the functional consequences of early stage of ankle arthropathy are difficult to define as early morphological and structural changes can be observed in clinically asymptomatic ankles. In this context, understanding biomechanics of the normal and arthritic foot is complex and difficult to quantify unless considering the foot as multiple functional segments using more sophisticated assessment tools such as multisegment foot models. However, this understanding can undoubtedly aid in the analysis of an underlying clinical problem and provide a strategic basis for a more optimal management. Aims: The purpose of this narrative review was firstly to revise information on the anatomy and biomechanics of the foot and ankle. Finally, related biomechanical markers of human motor performance, which are potentially implicated in the development of haemophilic ankle arthropathy, will be discussed based on published literature and expert opinion. Materials and methods: Searches in published literature were limited to the year 2000 onwards. Results: Although the ankle (tibiotalar joint) is the most commonly affected joint, associated subtalar joint (SJT) involvement is often seen. This would therefore imply that an alternative phraseology might be better. Discussion and conclusion: In this context, the authors propose the use of 'haemophilic tarsal pan‐arthropathy' (HTPA) which encompasses both tibiotalar and subtalar joints.